Molecular factors in the metabolism and pathogenicity of Phytophthora cinnamomi: characterization of RXLR family genes, Avr3a, and Avr1b - Boughanmi, Mohamed Belhassan (2021)
Mestrado de dupla diplomação com a Université Libre de Tunis